2022
DOI: 10.1139/cjas-2021-0038
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and post-weaning performance of piglets offered different types of creep feed

Abstract: We determined the impact of creep feed provision and type on pre- and post-weaning growth performance of piglets. At 2 weeks post-farrow, litters (n=50) were given no creep feed or provided a simple creep feed, a complex creep feed, or both until weaning at ~28 d. Creep feed, regardless of type, resulted in increased growth (P < 0.05) of piglets in the final week pre-weaning and immediate week post-weaning, which was not maintained at the end of the nursery period. Piglets showed no preference for creep fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Our systematic review identified a lack of information with respect to the ingredient composition of the creep feed, with only 35% of the studies detailing this information. This variable was shown to influence creep feed consumption, with positive impacts on piglet pre- and post-weaning performance [ 12 , 44 , 45 , 46 , 47 ]. Piglets offered a high-complexity creep diet in pellet form (30% pulverized oat groats and 25% spray-dried whey, 10% extruded soy protein concentrate, 6% spray-dried porcine plasma, 6% menhaden fish meal) had improved pre-weaning average daily gain and feed intake, and the proportion of creep feed eaters increased compared to piglets fed a simple diet in meal form (60% milo, 32% soybean meal, and 3% choice white grease).…”
Section: Discussionmentioning
confidence: 99%
“…Our systematic review identified a lack of information with respect to the ingredient composition of the creep feed, with only 35% of the studies detailing this information. This variable was shown to influence creep feed consumption, with positive impacts on piglet pre- and post-weaning performance [ 12 , 44 , 45 , 46 , 47 ]. Piglets offered a high-complexity creep diet in pellet form (30% pulverized oat groats and 25% spray-dried whey, 10% extruded soy protein concentrate, 6% spray-dried porcine plasma, 6% menhaden fish meal) had improved pre-weaning average daily gain and feed intake, and the proportion of creep feed eaters increased compared to piglets fed a simple diet in meal form (60% milo, 32% soybean meal, and 3% choice white grease).…”
Section: Discussionmentioning
confidence: 99%